A review of the intriguing interaction between testosterone and neurocognitive development in males with 47, XXY. Issue 2 (April 2020) - Samango-Sprouse, Carole A.; Yu, Christine; Porter, Grace F.; Tipton, Elizabeth S.; Lasutschinkow, Patricia C.; Gropman, Andrea L.
Abstract : Purpose of review: Although 47, XXY (Klinefelter syndrome) was first discovered more than 50 years ago, there have been limited comprehensive studies on this disorder. The present review explains the study of neurodevelopmental dysfunction and the impact of testosterone replacement at specific junctions in the life of males with 47, XXY. The intricate relationship between testosterone, neurodevelopment, health, and well being warrants an in-depth investigation in order to achieve optimal outcomes. Recent findings: Current literature suggests that the implementation of biological treatment has a positive impact on numerous areas of neurodevelopment. Further research is needed to determine ideal dosage, timing, and frequency of biological treatment for efficacy and safety of the child with 47, XXY. Summary: As noninvasive prenatal screening has detected increasing numbers of fetuses with 47, XXY, parents may benefit from both prenatal and postnatal counseling, including the latest innovative biological treatment, that may further optimize the child's outcome, especially when coupled with targeted early intervention services.